Development of a new method for the detection of vanadium complexes bound to DNA, using Agarose Gel Electrophoresis - Subedi, Prabal (2013)
Dissertação de mest., Qualidade em Análises, Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2012